Sostener la formación docente en tiempos de enseñanza remota de emergencia - Mastache, Anahí (2021)
This text is only possible based on the reflections shared by teachers and students of the subject Didáctica General (Professors' Training in Legal Science, UBA) in the three semesters experienced under the emergency remote teaching mode as result of the COVID-19 pandemic and the related decision to suspend face-to-face classes to be replaced by virtual lessons. Our objective is to share some decisions we have taken to keep the training process, the results obtained, the difficulties faced and, at the same time, to advance some ideas about the possibilities of taking advantage from these experiences in the future. To carry out this objective, we will use the information obtained from the teaching team (through videoconference meetings and WhatsApp exchanges) and from the students (through both structured surveys and informal comments in class situations, via e-mails or campus). Our analysis indicates that virtual teaching reinforced the importance of the approach, the emotional support, the task clarity and teamwork as key elements for training processes to take place. At first, we will explain the subject and its teaching proposal. Then, we will describe the main decisions made to face the change of scenario. Third, we will show achievements and difficulties. Finally, we will include some ideas for teaching the subject getting advantage from the best of face-to-face and virtual modalities